Effect of collagen sponge combined with epidermal growth factor in repairing maxillofacial head and neck wounds in rats: Collagen sponge and EGF promote wound healing - Wang, Qian; Wei, Zhiyi; Lin, Tianlai; Huang, Yazhen (Cellular and Molecular Biology, 2024)
Collagen sponge and epidermal growth factor (EGF) promote wound healing. However, the effect of collagen sponge combined with EGF in repairing maxillofacial head and neck wounds remains unclear. The rats were divided into 3 groups, including experimental group 1 (Vaseline gauze+EGF), experimental group 2 (collagen sponge+EGF) with control group (Vaseline+normal saline), and maxillofacial head and neck wounds were simulated. Wound pathological morphology was detected by HE staining; wound EGF, IL-1β, IL-6 along with TNF-α contents by ELISA and MMP1 level by western blot. At 7 and 14 days after treatment, wound healing rate of two experimental groups was higher than that of control group, and that of experimental group 2 presented higher than that of experimental group 1. Compared with control group, experimental group 1 had significantly fewer inflammatory cells in the wound tissue, local erythrocyte spillage outside the vascular walls, more collagen deposition and more granulation tissue. Compared with experimental group 1, inflammatory cells in wound tissues of experimental group 2 were significantly reduced, the collagen tissues were visible and arranged, and the growth of the wound granulation tissue was obvious. IL-1β, IL-6 along with TNF-α levels in two experimental groups presented lower than control group, and EGF level was higher. More importantly, in contrast to experimental group 1, IL-1β, IL-6 along with TNF-α in experimental group 2 presented lower, and EGF level presented higher. At 14 days after treatment, MMP1 level in two experimental groups was lower than control group. In contrast to experimental group 1, MMP1 level in experimental group 2 was lower. In summary, collagen sponge combined with EGF for the first time significantly improved the healing speed of maxillofacial head and neck wounds and reduced the scar left after wound healing.